Didactic Visual Narrations in Nepali Manuscript Illuminations - Sharma, Yam Prasad (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
Manuscript illuminations are the early forms of traditional Nepali paintings. Manuscript illuminations are the miniature paintings found in the manuscripts, the handwritten religious texts and treaties on ethics. Such paintings tell the mythical stories in visual form. Some manuscript illuminations present the characters and events in such a way that they tell moral stories using visual medium. Sometimes, the contents appear in the form of fable. The animals are personified, for they act and behave like a human being. In some cases, the visual narration is allegorical in the sense that one set of characters, setting and events stand for other characters, place and activities. Although some characters are animals and supernatural beings, they reflect on this world, human beings and objects in the world. Such paintings explore real world, human experiences and moral values through strange, unusual and de-autometized art forms. The paintings attempt to create moral order in the then contemporary society. This article traces such issues and themes in narrative paintings found in manuscripts like Vishnudharma, Shivadharma, Devimahatmya, Pancaraksa, VesantaraJataka and Hitopadesa.